Healthcare-Associated Infections: Epidemiology, Diagnostics, and Management in Internal Medicine - Pricilla Putri Derlian Dohude; Novrina Situmorang (Universitas Methodist Indonesia, 2025)
Background: Nosocomial infections, particularly those occurring after 72hours of patient admission, present a serious challenge in hospitals. Thesegram-negative bacteria, including Escherichia coli, Klebsiellapneumoniae, and Shigella, can lead to various infections such as urinarytract infections and nosocomial pneumonia. Nosocomial pneumonia,which encompasses Hospital-Acquired Pneumonia (HAP) and Ventilator-Associated Pneumonia (VAP), is associated with high mortality rates andcan spread through contact transmission. The primary causes of theseinfections include prolonged hospitalization, severity of illness, andexcessive use of antibiotics, which can enhance bacterial resistance. Toprevent the spread of nosocomial infections, stringent hygiene practicesand proper aseptic procedures are essential, along with prudent antibioticmanagement based on laboratory results. These preventive measures arecrucial for improving the quality of healthcare services in hospitals andreducing the risk of nosocomial infections